A shared urban project and influential actors : Case of the South land-use plan in Guelma - Cheraitia, Mohammed; MAHIMOUD , Aissa (Journal of Human Sciences, 2021)
The southern extension of Guelma city was made by its largest POS, which is the subject of the development of more than 4000 collective dwellings. The challenges of this POS were multiple as the strategies undertaken by the different actors aiming to preserve their interest in occupying the sol. This article questions the urban public planning under the influence of the participation and the concertation concepts; where an emphasis was given to the particular role of its actors namely the public authorities, developers as well as the future co-owners of dwellings. This work focuses on the organization of this participation, and the strategies of the actors in the management with often contradictory interests. Modifications were made on the project by the promoters, and changes were made by future buyers inside and outside the dwellings, these are some indicators explaining the complexity of urban practices that require the shared urban project approach as a solution. The approach of future co-owners of collective dwellings carried out by a survey will be necessary to highlight the complexity of urban actions and clarify the strategies adopted by the act